The Diagnostic Value of MRI for High Ankle Sprains with an Unstable Syndesmosis: Time to Scan Matters. Issue 4 (16th October 2019) - Marsland, Daniel; Randell, Matthew; Ballard, Emma; Forster, Ben; Lutz, Michael
Category: Ankle, Arthroscopy, Sports, Trauma Introduction/Purpose: Early clinical examination combined with MRI following a high ankle sprain allows accurate diagnosis of syndesmosis instability. However, patients often present late, and for chronic injuries clinical assessment is less reliable. The aims of the current study were to describe MRI characteristics associated with diagnosed syndesmosis instability, and to assess if MRI characteristics change as the injury becomes chronic. Methods: Patients with a high ankle sprain and proven syndesmosis instability at arthroscopy were retrospectively identified from the logbooks of two fellowship trained foot and ankle surgeons over a five-year period. Patients were excluded if they had a distal fibula fracture or absence of an MRI report by a consultant radiologist. Associations between MRI characteristics and time from injury to MRI scan, categorised as acute (< 6 weeks), intermediate (6-12 weeks) and chronic (> 12 weeks) were examined using the Pearson's chi-squared or Fisher's exact tests (significance set at p<0.05). Results: Of the 164 patients, 108 had an MRI scan in the acute period, 32 were classified as intermediate and 24 as chronic. A posterior syndesmosis injury was detected in 93.5% of acute patients, 87.5% of intermediate patients and 54.2% of chronic patients. In the acute group, PITFL injury was detected in 78.7% of patients, posterior malleolus bone oedema in 60.2% and posterior malleolus fracture in 15.7%. The proportion of patients with injury to the PITFL in intermediate patients was 59.4% and 29.2% in chronic patients which was significantly lower than in acute patients (p<0.001). Twenty eight patients with posterior malleolus bone oedema had an apparently normal PITFL. The proportion of patients with posterior malleolus bone oedema or fracture were not significantly different between groups. Conclusion: The most important finding of the current study is that in acute high ankle sprains with syndesmosis instability, MRI detected a posterior syndesmosis injury in 93.5% of patients. Posterior malleolus bone oedema appears to be a marker of an unstable syndesmosis injury, regardless of time from injury to the MRI scan. The ability of MRI to detect a posterior syndesmosis injury reduces significantly if delayed more than 12 weeks. If suspicious of a high ankle sprain, we advocate early MRI assessment to help determine stable versus unstable injuries, as the ability of MRI to detect posterior injuries reduces over time.